EFFORTS TO IMPROVE MOVEMENT CREATIVITY IN CHILDREN WITH SPECIAL NEEDS THROUGH THE IMPLEMENTATION OF SIMPLE GAME MODELS BASED ON GAME-BASED LEARNING IN PHYSICAL EDUCATION SUBJECTS FOR CLASS I-A STATE ELEMENTARY SCHOOL 2 LOKTABAT SELATAN - Irmayanti; Rahmadi; Fakhrudin; Sujarwoko; Fani Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of a simple game model based on Game-Based Learning (GBL) and to improve the movement creativity of students with special needs (SEN) in the PJOK subject for grade I-A at SDN 2 Loktabat Selatan. This study uses a Classroom Action Research (CAR) approach with the Kemmis and McTaggart spiral model, conducted in two cycles. The research subjects are 4 SEN students with characteristics of slow learners and mild concentration disorders. Data collection was carried out through observation of student activity and tests of creative movement skills. The sampling technique used purposive sampling based on the results of the initial identification. Data analysis used a comparative descriptive approach between pre-cycle, cycle I, and cycle II. The research results showed a significant increase in each cycle. The average score of creative movement skills tests increased from 53.13 (pre-cycle) to 67.97 (cycle I) and 76.56 (cycle II), with classical completeness increasing from 0% to 50% and 75%. Learning activeness increased from 40.00 (Less Active) to 58.75 (Quite Active) and 72.50 (Active). It was concluded that the simple game model based on GBL effectively improves movement creativity and learning activeness of students with special needs in PJOK learning.